An Analysis of Constraints to Economic and Trade Cooperation between the China-Africa Community with a Shared Future - Debongo Devincy Yanne Sylvaire (International Journal of Engineering and Management Research, 2020)
The constraints in the economic and trade cooperation of the China-Africa community of shared future that cannot neglect. The main constraints to the development of China-Africa economic cooperation include the imbalance of China-Africa economic and trade, the unitary commodity structure, and competition in the international market. There are differences in the political and legal values between China and Africa. Western developed countries restrict and exclude the economic cooperation between the Chinese and African communities, fabricate the China threat theory, and seek energy and political interests to disrupt the smooth development of China-Africa economic and trade cooperation.